2021
DOI: 10.5829/ije.2021.34.08b.16
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pin Geometry and Tool Rotational Speed on Microstructure and Mechanical Properties of Friction Stir Spot Welded Joints in AA2024-O Aluminum Alloy

Abstract: In the present study, the effects of pin geometry and tool rotational speed on the microstructure and mechanical characteristics of the AA2024-O friction stir spot welding (FSSW) joint were investigated.Two different types of pin geometries, namely cylindrical and step pins, and three different rotational speeds of 900, 1400, and 1800 rpm were used in the friction stir spot welding joint. The microstructure observation, hardness measurements, and shear tests were conducted. Results showed that both pin geometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…Conversely, the AA2024 alloy is extensively employed in the aerospace and automotive sectors. Although the annealed version AA2024-O is not directly recommended for use, efforts have been made to explore the advantages of its aging behavior for joining and forming processes [36,37]. Some research has shown satisfactory mechanical and corrosion properties for welded joints in both AA6061-O [38,39] and AA2024-O [40,41] alloys.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, the AA2024 alloy is extensively employed in the aerospace and automotive sectors. Although the annealed version AA2024-O is not directly recommended for use, efforts have been made to explore the advantages of its aging behavior for joining and forming processes [36,37]. Some research has shown satisfactory mechanical and corrosion properties for welded joints in both AA6061-O [38,39] and AA2024-O [40,41] alloys.…”
Section: Introductionmentioning
confidence: 99%
“…The width of the onion substructure decreases with increased rotational speed. Both fragmentation and redistribution of intermediate phases were associated with increased rotational speed and corrosion resistance, correlating this with the reduction of sites susceptible to corrosion attack [36]. Finally, Sasikumar et al [48] evaluated the effects of process parameters on mechanical properties and corrosion resistance on filler-induced friction stir welding of dissimilar AA6082-AA5052 joints.…”
Section: Introductionmentioning
confidence: 99%
“…The lower cost reduced weight by joining light-weight metals with metallurgical features, and a reduced requirement for skilled people make FSW an attractive welding technique [3]. Moreover, the higher energy efficiency and eco-friendliness make FSW a "green" procedure [4]. Utilizing this welding technique, it becomes possible to decrease energy consumption by 99% and installation cost by 40% compared to resistance spot welding [5].…”
Section: Introductionmentioning
confidence: 99%
“…The process has some disadvantages such as the low welding speed, heavy welding loads on the tool [4]. The enhancement in the plastic material flow have been investigated [5][6][7][8]. Mabrouk et al [9] used a mathematical model to express the heat generation during ultrasonic vibration improved friction stir welding process.…”
Section: Introductionmentioning
confidence: 99%